Magnetic Activity Evolution of Solar-like Stars. II. Sph–Ro Evolution of Kepler Main-sequence Targets - Savita Mathur; Ângela R. G. Santos; Zachary R. Claytor; Rafael A. García; Antoine Strugarek; Adam J. Finley; Quentin Noraz; Louis Amard; Paul G. Beck; Alfio Bonanno; Sylvain N. Breton; Allan S. Brun; et al. (The Astrophysical Journal)
There is now a large sample of stars observed by the Kepler satellite with measured rotation periods and photometric activity index S _ph . We use this data, in conjunction with stellar interiors models, to explore the interplay of magnetism, rotation, and convection. Stellar activity proxies other than S _ph are correlated with the Rossby number, Ro, or ratio of rotation period to convective overturn timescale. We compute the latter using the Yale Rotating Evolution Code stellar models. We observe different S _ph –Ro relationships for different stellar spectral types. Though the overall trend of decreasing magnetic activity versus Rossby number is recovered, we find a localized dip in S _ph around Ro/Ro _⊙  ∼  0.3 for the G and K dwarfs. F dwarfs show little to no dependence of S _ph on Rossby number due to their shallow convective zone, further accentuated as T _eff increases. The dip in activity for the G and K dwarfs corresponds to the intermediate rotation period gap, suggesting that the dip in S _ph could be associated with the redistribution of angular momentum between the core and convective envelope inside stars. For G-type stars, we observe enhanced magnetic activity above the solar Rossby number. Compared to other Sun-like stars with similar effective temperature and metallicity, we find that the Sun’s current level of magnetic activity is comparable to its peers and lies near the transition to increasing magnetic activity at high Rossby number. We confirm that metal-rich stars have a systematically larger S _ph level than metal-poor stars, which is likely a consequence of their deeper convective zones.